2014
DOI: 10.1111/echo.12687
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Measurement of Tricuspid Annular Plane Systolic Excursion in Children: Can It Substitute for an M‐Mode Assessment?

Abstract: MM-TAPSE and 2D-TAPSE correlate strongly, with 2D-TAPSE being consistently about 1 mm less than values obtained by the M-mode technique. We conclude that 2D-TAPSE can provide a reliable alternative to MM-TAPSE to quantitatively measure right ventricular systolic function and may be especially useful in situations where retrospective comparisons are sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Thus, TAPSE was measured offline (blinded to treatment group) from the apical four chamber view by subtracting the distance between the lateral tricuspid leaflet annular insertion and sector apex in systole from the distance between the two in diastole. We and others have previously validated this technique 2, 12 and the normal values, clinical correlates and prognostic implications of 2-D TAPSE measured offline in 500 patients with HFpEF have been defined. 2 Intra- and Inter-observer variability for 2D TAPSE and the correlation between 2-D and M-mode measured TAPSE have been defined 2 (Supplemental Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, TAPSE was measured offline (blinded to treatment group) from the apical four chamber view by subtracting the distance between the lateral tricuspid leaflet annular insertion and sector apex in systole from the distance between the two in diastole. We and others have previously validated this technique 2, 12 and the normal values, clinical correlates and prognostic implications of 2-D TAPSE measured offline in 500 patients with HFpEF have been defined. 2 Intra- and Inter-observer variability for 2D TAPSE and the correlation between 2-D and M-mode measured TAPSE have been defined 2 (Supplemental Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The currently available age‐based normal reference values are for M‐mode TAPSE. Although 2D TAPSE has been shown to have a strong correlation with that derived by M‐mode, its values are consistently about 1 mm less than those obtained by M‐mode . To account for this known variability between M‐mode and 2D TAPSE, further subanalysis was performed by adding 1 mm to the 2D TAPSE values to avoid any overestimation of RVSD.…”
Section: Methodsmentioning
confidence: 99%
“…To account for the correlation between M‐mode TAPSE and 2D TAPSE, a sensitivity analysis was performed. A recent study suggests that there is a reliable correlation between M‐mode TAPSE and 2D TAPSE with a mean difference of 1 mm . Therefore, the sensitivity analysis includes the addition of 1 mm to the measured 2D TAPSE to account for the variability between 2D TAPSE and M‐mode TAPSE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, TAPSE has been measured by M‐mode (MM‐TAPSE) as the displacement of the tricuspid valve hinge point (TVHP). A recent study demonstrated that retrospective measurement of excursion of the TVHP on two‐dimensional (2D) imaging in an apical 4‐chamber view (2D‐TAPSE) correlates well with MM‐TAPSE . We have developed a semiautomatic technique that uses active contour models for the evaluation of TAPSE (SA‐TAPSE) using 2D apical 4‐chamber image.…”
mentioning
confidence: 99%